Effect of brexpiprazole on control of impulsivity in schizophrenia: A randomized functional magnetic resonance imaging study. (30th July 2020) - van Erp, Theo GM; Baker, Ross A; Cox, Kevin; Okame, Takao; Kojima, Yoshitsugu; Eramo, Anna; Potkin, Steven G
Highlights: Impulsivity is a treatment target in schizophrenia, to minimize harmful behaviors. Impulsivity is associated with functional and structural brain changes. Patients receiving brexpiprazole completed impulsivity tasks during fMRI scans. Beneficial changes in inhibition-related brain activation and behavior were seen. Abstract: Impulsivity in schizophrenia is a risk factor for suicide, drug abuse, and other risk-taking behaviors. This exploratory, multicenter, randomized, double-blind, functional magnetic resonance imaging (fMRI) study assessed the effects of brexpiprazole on brain regions that control impulsive behavior. Thirty-eight outpatients with stable schizophrenia and impulsivity symptoms were randomized to 6 weeks of brexpiprazole 2 or 4 mg/day. The prespecified outcome measure was blood oxygen-level dependent (BOLD) activation in the right ventrolateral prefrontal cortex (VLPFC) during performance of tasks associated with inhibition/control of impulsivity: the go/no-go task and stop-signal task. Secondary objectives evaluated the efficacy, safety and tolerability of brexpiprazole. Over 6 weeks, patients receiving brexpiprazole had no statistically significant change in right VLPFC BOLD activation during the go/no-go task, but showed a significant decrease in right VLPFC BOLD activation during the stop-signal task. Brexpiprazole was also associated with significantly improved stop-signal reaction time (SSRT). No worsening of psychiatric symptoms, functioning, or impulsivity occurred in these patients. No unexpected safety or tolerability concerns were identified. In conclusion, brexpiprazole treatment among patients with schizophrenia and impulsivity was associated with decreased right VLPFC activation and decreased SSRT, supportive of a benefit of brexpiprazole on inhibition-related brain activation and behavior. ClinicalTrials.gov identifier: NCT02194933.